2020
DOI: 10.33403/rigeo.719222
|View full text |Cite
|
Sign up to set email alerts
|

A Search for a Method to Improve Critical Thinking Skills in Social Studies Teaching: Writing-to-Learn

Abstract: The aim of this study is to investigate the effects of using multiple writing-to-learn activities on the critical thinking skills and dispositions of prospective teachers. For this purpose, the current study employed an embedded mixedmethods design and was carried out with 34 prospective Social Studies teachers who are studying at a public university. Research data were collected with the California Critical Thinking Disposition Inventory, as well as using the Holistic Critical Thinking Scoring Rubric, and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This parallels other results from the literature (e.g. Adanali & Alim, 2017, 2019Hanifah et al, 2015;Seyhan, 2019. Through EBL, students are able to see the application of content that they would otherwise just read about in a textbook (Fögele, 2015;Higginbottom, 2016;Kayaalp et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…This parallels other results from the literature (e.g. Adanali & Alim, 2017, 2019Hanifah et al, 2015;Seyhan, 2019. Through EBL, students are able to see the application of content that they would otherwise just read about in a textbook (Fögele, 2015;Higginbottom, 2016;Kayaalp et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…To remedy these shortcomings, training program should include activities that encourage instructors to analyze and comprehend research findings as well as exercises that improve critical thinking abilities (Kayaalp et al, 2020). Facilitators should guide participants in synthesizing knowledge from many sources and generating sound judgements.…”
Section: Discussionmentioning
confidence: 99%
“…There are some previous studies that support a positive relationship between social studies and critical thinking, such as the research that found significant relationship between critical thinking and critical thinking dispositions of the Social Studies subject (Kayaalp et al, 2020). Then, there is bound interaction between investigation, equity, and student cohesiveness aspects of social studies learning environment and students' critical thinking disposition (Meral & Tas, 2017).…”
Section: Introductionmentioning
confidence: 96%